2010
DOI: 10.1159/000318191
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes of Fetal Abdominal Cysts and Comparison of Prenatal and Postnatal Diagnoses

Abstract: Introduction: The differential diagnosis of an abdominal cyst can be challenging, and an accurate diagnosis is crucial for optimal antenatal management. The aim of this study was to compare the ante- and postnatal diagnoses of cases with abdominal cyst and to determine the diagnostic accuracy of ultrasonography. Material and Methods: A database review was performed regarding the diagnosis of fetal abdominal cyst covering the period 2002–2009. Structural characteristics and localizations of the cysts in the abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 24 publications
5
31
1
3
Order By: Relevance
“…Accordingly, Özyüncü et al reported overall spontaneous mortality rate to be 11/64 (17%). Intrauterine deaths in our series were 2/17 (11.8%), while this was found to be 3.6% and 4.2% in previous reports, respectively (1,21). We think this difference arises from the inclusion criteria of the study groups.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Accordingly, Özyüncü et al reported overall spontaneous mortality rate to be 11/64 (17%). Intrauterine deaths in our series were 2/17 (11.8%), while this was found to be 3.6% and 4.2% in previous reports, respectively (1,21). We think this difference arises from the inclusion criteria of the study groups.…”
Section: Discussioncontrasting
confidence: 75%
“…The most common antenatal diagnosis was ovarian cyst. Ovarian cyst cases were diagnosed at an average of 30.13±5.59 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] gestational weeks. Diagnosis was confirmed as ovarian cyst at 6 of the 8 cases postnatally.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been reported that a specific diagnosis does not influence the management of patients with cystic lesions, in our study, all cases that remained undiagnosed after birth did not have a specific prenatal diagnosis. In literature, it has been reported that 17% to 24% of fetal abdominal cysts may resolve during intrauterine life and these data might be considered for a correct management and counseling. In a similar series, Ozyuncu et al reported a spontaneous resolution in 12 of 71 cases (16.9%: duodenal atresia in one, mesenteric cyst in one, ovarian cyst in four, megacystis in two, renal cyst in two, hepatic cyst in two and choledochal cyst in one).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, it has been reported that 17% to 24% of fetal abdominal cysts may resolve during intrauterine life and these data might be considered for a correct management and counseling. In a similar series, Ozyuncu et al reported a spontaneous resolution in 12 of 71 cases (16.9%: duodenal atresia in one, mesenteric cyst in one, ovarian cyst in four, megacystis in two, renal cyst in two, hepatic cyst in two and choledochal cyst in one). In our series, spontaneous resolution during pregnancy occurred in 5.5% of cases (two hepatic and two ovarian cysts).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of the neonatal course is impossible as it varies from complete resolution to life-threatening complications 1. Common cysts include those arising from the gastrointestinal tract and the genitourinary tract 2. Cysts arising from the testis is a difficult diagnosis to make both prenatally and postnatally.…”
Section: Introductionmentioning
confidence: 99%